Enhancement of growth and Cannabinoids content of hemp (Cannabis sativa) using arbuscular mycorrhizal fungi - Seemakram, Wasan; Paluka, Jakkapat; Suebrasri, Thanapat; Lapjit, Chanon; Kanokmedhakul, Somdej; Kuyper, Thomas W.; Ekprasert, Jindarat; Boonlue, Sophon (Frontiers in Plant Science, 2022)
This study aimed to investigate the efficiency of arbuscular mycorrhizal fungi (AMF) to promote growth and cannabinoid yield of Cannabis sativa KKU05. A completely randomized design (CRD) was conducted with six replications for 60 days. Two different species of AMF, Rhizophagus prolifer PC2-2 and R. aggregatus BM-3g3 were selected as inocula and compared with two non-mycorrhizal controls, one without synthetic fertilizer and one with synthetic NPK fertilizer. The unfertilized non-mycorrhizal plants had the lowest performance, whereas plants inoculated with R. aggregatus BM-3g3 performed best, both in terms of plant biomass and concentrations of CBD and THC. There were no significant differences in plant biomass and cannabinoid concentrations between non-mycorrhizal plants that received synthetic fertilizer and mycorrhizal plants with inoculum of R. prolifer PC2-2Our data demonstrate the great potential for cannabis cultivation without risking deterioration of soil structure, such as soil hardening and increased acidity, which might be induced by long-term use of synthetic fertilizer.